Inconvenient relationship of haemoglobin A1c level with endothelial function in type 2 diabetes in a cross-sectional study. Issue 6 (9th June 2021) - Yamaji, Takayuki; Harada, Takahiro; Hashimoto, Yu; Takaeko, Yuji; Kajikawa, Masato; Han, Yiming; Maruhashi, Tatsuya; Kishimoto, Shinji; Hashimoto, Haruki; Kihara, Yasuki; Hida, Eisuke; Chayama, Kazuaki; et al.
Abstract : Objective: The aim of this study was to determine the relationship of haemoglobin A1c (HbA1c) level with flow-mediated vasodilation (FMD) and nitroglycerine-induced vasodilation (NID) in patients with type 2 diabetes. Design: Cross-sectional study. Setting: 22 university hospitals and affiliated clinics in Japan. Participants: 1215 patients with type 2 diabetes including 349 patients not taking antidiabetic drugs. Measures: We evaluated FMD and HbA1c level. All patients were divided into four groups based on HbA1c level: <6.5%, 6.5%–6.9%, 7.0%–7.9% and ≥8.0%. Results: An inverted U-shaped pattern of association between HbA1c level and FMD was observed at the peak of HbA1c of about 7%. FMD was significantly smaller in the HbA1c <6.5% group than in the HbA1c 6.5%–6.9% group and HbA1c 7.0%–7.9% group (p<0.001 and p<0.001), and FMD values were similar in the HbA1c <6.5% group and HbA1c ≥8.0% group. There were no significant differences in NID values among the four groups. After adjustments for confounding factors, FMD was significantly smaller in the HbA1c <6.5% group than in the HbA1c 6.5%–6.9% and HbA1c 7.0%–7.9% group (p=0.002 and p=0.04). In patients not taking antidiabetic drugs, FMD was also significantly smaller in the HbA1c <6.5% group than in the HbA1c 6.5%–6.9% group and HbA1c 7.0%–7.9% group (p<0.001 and p=0.02), and there were no significant differences in NID values among the four groups. Conclusions: These findings suggest that there is an inverted U-shaped pattern of association between FMD and HbA1c and that a low HbA1c level of <6.5% is associated with endothelial dysfunction. Trial registration number: UMIN000012950, UMIN000012951, UMIN000012952 and UMIN000003409.